2020
DOI: 10.1021/acsnano.0c06595
|View full text |Cite
|
Sign up to set email alerts
|

Aging of Self-Assembled Lead Halide Perovskite Nanocrystal Superlattices: Effects on Photoluminescence and Energy Transfer

Abstract: Excitonic/electronic coupling and cooperative interactions in self-assembled lead halide perovskite nanocrystals were reported to give rise to a collective low energy emission peak with accelerated dynamics. Here we report that similar spectroscopic features could appear as a result of the nanocrystal reactivity within the self-assembled superlattices. This is demonstrated by using CsPbBr3 nanocrystal superlattices under room temperature and cryogenic micro-photoluminescence spectroscopy. It is shown that keep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 115 publications
(245 reference statements)
4
81
1
Order By: Relevance
“…We do note that the energies of the absorption and PL peaks of the SBs are close to values typically found for CsPbBr 3 thin films, which is expected to be around 2.35 eV. 19 , 20 Furthermore, while the Stokes shift for NCs is ∼80 meV, for the SBs it decreases to ∼20 meV, which is in line with the value of bulk CsPbBr 3 . 21 A schematic of the differences in absorption and emission is given in Figure 1 e. Baranov et al observed a large red shift of an aged superlattice sample comprising 8 nm sized NCs as compared to the individual NCs, which they suggested to be related to bulk-like CsPbBr 3 particles formed by fused NCs in the superlattice.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…We do note that the energies of the absorption and PL peaks of the SBs are close to values typically found for CsPbBr 3 thin films, which is expected to be around 2.35 eV. 19 , 20 Furthermore, while the Stokes shift for NCs is ∼80 meV, for the SBs it decreases to ∼20 meV, which is in line with the value of bulk CsPbBr 3 . 21 A schematic of the differences in absorption and emission is given in Figure 1 e. Baranov et al observed a large red shift of an aged superlattice sample comprising 8 nm sized NCs as compared to the individual NCs, which they suggested to be related to bulk-like CsPbBr 3 particles formed by fused NCs in the superlattice.…”
Section: Resultssupporting
confidence: 87%
“… 21 A schematic of the differences in absorption and emission is given in Figure 1 e. Baranov et al observed a large red shift of an aged superlattice sample comprising 8 nm sized NCs as compared to the individual NCs, which they suggested to be related to bulk-like CsPbBr 3 particles formed by fused NCs in the superlattice. 20 The small red shift that we observe in the freshly produced SBs in solution suggests there is no such coalescence or bulk formation due to such an aging effect. This is further supported by the larger photon energy, although moderately, than that reported for bulk perovskites.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…2.3 eV, 535–540 nm) as well as a very strong quenching of the red aggregate band already at intermediate temperatures would hardly be reconcilable with an alternative assumption that the red-shifted emission peak could originate from the bulk material forming during the aggregation process. 78 The latter would imply an order of magnitude reduction of bulk emission quantum yield just within this temperature range.…”
Section: Results and Discussionmentioning
confidence: 95%
“…The quantum dots (QDs) superlattice is based on QDs, which are self-assemble under the microscopic weak interaction force to form a long-range ordered 3D structure. [12][13][14][15][16] Its unique internal structure can trigger macroscopic quantum coupling effects, collective effects, and synergistic effects, [9][10][11][12]14,[17][18][19] which can also speed up the radiation rate. Therefore, the QDs superlattice microcavity reveals unique optical properties, cavity-enhanced superfluorescence (CESF) behavior.…”
Section: Introductionmentioning
confidence: 99%